EARLY TRACES HINDU-BUDDHIST INFLUENCE ALONG THE NORTH COAST OF CENTRAL JAVA: ARCHAEOLOGICAL SURVEY OF THE DISTRICT OF BATANG - Agustijanto Indradjaja; Véronique Degroot (Badan Riset dan Inovasi Nasional, 2014)
Abstract. In Coastal Central Java, archaeological research dealing with the Hindu-Buddhist period is almost always focused on the coastal area between Kedu and Yogyakarta, which was controlled by the Matāram Kingdom around the 8-9th Century AD. Research that attempts to investigate and reconstruct the social conditions of coastal communities during the pre-Matāram period has yet to be undertaken. This paper is such an attempt. It explores Hindu-Buddhist remains in the Batang District, a district which, we believe, was an important entry point for Hindu-Buddhist traditions prior to the emergence of the Matāram Kingdom in the hinterland of Central Java. Data collected through the survey, further archaeological data relevant will be conducted descriptive analysis to answer questions in the study. The survey results have identified a number of important findings such as statues, temples and inscriptions ranging from coastal areas to inland Batang. Based on the identification of a number of archaeological findings it apparent that the area in Batang already appear influence of Hindu-Buddhist long before the emergence of the ancient Matāram Kingdom around the 8th Century AD. Keywords: Archaeological survey, Batang, Hindu-Buddha, North Coast. Abstrak. Jejak awal Pengaruh Hindu-Buddha di Sepanjang Pantai Utara Jawa Tengah: Survei Arkeologi di Kota Batang. Penelitian arkeologi di pantai utara Jawa Tengah mengenai kehidupan masa Hindu-Buddha hampir selalu dipusatkan pada wilayah antara Kedu-Yogyakarta, yang dikuasai oleh Kerajaan Matāram pada sekitar abad ke-8–9 Masehi. Penelitian yang berupaya mempelajari dan merekonstruksi kondisi sosial masyarakat di daerah pesisir masa pra-Matāram selama ini belum pernah dilakukan. Karya tulis ini berusaha melakukan eksplorasi pada masa pra-Matāram di Jawa Tengah, khususnya di Kabupaten Batang yang diduga sebagai salah satu daerah yang penting pada awal periode sebelum munculnya Kerajaan Matāram di pedalaman Jawa Tengah. Pengumpulan data dilakukan melalui survei, selanjutnya data arkeologi yang relevan dilakukan analisis deksriptif untuk menjawab pertanyaan di dalam penelitian. Hasil survei berhasil mengidentifikasikan sejumlah temuan penting seperti arca, candi dan prasasti mulai dari wilayah pesisir sampai pedalamanan Kabupaten Batang. Berdasarkan identifikasi sejumlah temuan arkeologi tersebut tampak bahwa wilayah Batang sudah mendapat pengaruh Hindu-Buddha jauh sebelum munculnya Kerajaan Matāram kuna sekitar abad ke-8 M. Kata Kunci: Survei arkeologi, Batang, Hindu-Buddha, Pantai Utara